2021
DOI: 10.1080/01587919.2021.1885092
|View full text |Cite
|
Sign up to set email alerts
|

Building resilience in education systems post-COVID-19

Abstract: Building resilience in education systems post-COVID-19Few developments in recent memory have rattled the zeitgeist of contemporary educational systems as has the COVID-19 pandemic. From early childhood education to postgraduate study, the resilience of education systems all over the world is being tested. Primarily, this has to do with the adequacy of conventional campus-based learning and teaching operations, as well as the reskilling and upskilling of learners and teachers for a dramatically altered and nont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 5 publications
3
32
0
7
Order By: Relevance
“…However, our results showed that no significant differences were found before and after pandemic. This has also been observed in other students from different countries, and the reason that these studies highlighted was the resilience of both lecturers and students [66], [69]. Students from different Asiatic universities showed a high level of satisfaction towards learning during pandemic [66].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, our results showed that no significant differences were found before and after pandemic. This has also been observed in other students from different countries, and the reason that these studies highlighted was the resilience of both lecturers and students [66], [69]. Students from different Asiatic universities showed a high level of satisfaction towards learning during pandemic [66].…”
Section: Discussionsupporting
confidence: 67%
“…Students from different Asiatic universities showed a high level of satisfaction towards learning during pandemic [66]. On the one hand, resilience is thought to be the result of perseverance and passion [69]. On the other hand, it could also be the result of flexibility, both in terms of location (students can follow the online sessions anywhere) and of time (students can adjust learning times and watch the lectures many times) [70].…”
Section: Discussionmentioning
confidence: 99%
“…This may be because all three universities, where this study was conducted, had provided access to recorded lectures and other materials via the Learning Management System so that even those students who do not have access to a reliable Internet connection to attend synchronous sessions can be engaged in online learning. Even though the poor Internet connectivity can be a challenge that they encounter, the mere existence of challenges may not always hamper student motivation in online education as distance learners are naturally more self-resilient and motivated [75]. Even in a recent study, Dhinigra, Pasricha, Sthapak and Bhatnagar (2021) [68] report that most of the medical students that they surveyed in India had the motivation to receive online education despite various challenges they had encountered.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, several studies reported that the learners might not feel advantageous with e-learning due to unexpected readiness, e.g. lower confidence, lower technological skills, and poor internet access [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%